2017
DOI: 10.1186/s41043-017-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of hypertension management in Asmara, Eritrea: patients’ perspectives

Abstract: BackgroundPersonal hypertension management is a cornerstone in the prevention of hypertension complications. In Eritrea, the increase in the national life expectancy rate has been accompanied by an increase in hypertension complications such as stroke. Hence, this study was designed to identify barriers and facilitates to hypertension management from the perspective of the patients.MethodsThis was a qualitative study of a total of 48 individual in-depth interviews and two focus group discussions. It was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 27 publications
8
43
0
Order By: Relevance
“…Previous studies have shown that family and community support act as a main enabler for treatment adherence [ 25 27 ] and lack of access to such support systems as one of the major causes of non-adherence among TB patients [ 28 ]. In this study, the majority of the patients did not receive social or financial support from their family or their community.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that family and community support act as a main enabler for treatment adherence [ 25 27 ] and lack of access to such support systems as one of the major causes of non-adherence among TB patients [ 28 ]. In this study, the majority of the patients did not receive social or financial support from their family or their community.…”
Section: Discussionmentioning
confidence: 99%
“…Although drug treatment has precise indications, the adoption of a healthy lifestyle is strongly suggested as a coadjuvant for the control of hypertension, with emphasis on the regular practice of physical activity, healthy eating, smoking cessation, and reduced alcohol consumption 28 , 29 . This indication is based on evidence that these behaviors may reduce blood pressure levels, improve the effect of antihypertensive medication, and decrease cardiovascular risk, and this effect is intensified when two or more practices are combined 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Special attention should be given to the control of hypertension attributed to background, indicating that among both women (33.7%) and men (63.7%), hypertension control is attributed to other factors, such as schooling, socioeconomic status, obesity, and others, which are widely described in the literature as associated with hypertension control 2,10,20,28 , but which were not the focus of the current study. In addition, the drug treatment variable used in ELSI-Brasil was based on the participant's self-report and does not mean that the reported treatment was followed according to the medical prescription.…”
Section: Discussionmentioning
confidence: 92%
“…Next to moderate alcohol consumption, regular physical activity was the health behavior that most contributed to hypertension control, both in the total sample and in men and women. Various studies have evidenced the positive association between physical activity and blood pressure control 10,18,19,33 . The current study corroborates these results, quantifying the contribution of physical activity to hypertension control and highlighting the importance of maintaining physical activity at recommended levels among hypertensive individuals, as an important adjuvant to medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation